2018
DOI: 10.1371/journal.pone.0193619
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between anhedonia, suicidal ideation and suicide attempts in a large sample of physicians

Abstract: BackgroundThe relationships between anhedonia and suicidal ideation or suicide attempts were explored in a large sample of physicians using the interpersonal psychological theory of suicide. We tested two hypotheses: firstly, that there is a significant relationship between anhedonia and suicidality and, secondly, that anhedonia could mediate the relationships between suicidal ideation or suicide attempts and thwarted belongingness or perceived burdensomeness.MethodsIn a cross-sectional study, 557 physicians f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 45 publications
5
66
0
3
Order By: Relevance
“…() suggest that a more precise distinction can be found when focusing on recent changes in anhedonia, which is more accurately captured by the Specific Loss of Interest and Pleasure Scale (SLIPS) and the Beck Depression Inventory's (BDI) anhedonia subscale (items 4, 12, and 21). Several of the studies indicating a positive relationship between anhedonia and STB used these measures (Gabbay et al., ; Loas, Lefebvre, Rotsaert, & Englert, ; Winer et al., ; Winer, Drapeau, Veilleux, & Nadorff, ; Yaseen et al., ; Zielinski et al., ), providing support for the hypothesis that increased risk of STB is associated with acute anhedonic state. However, these studies do not address the role of trait anhedonia.…”
Section: Introductionmentioning
confidence: 95%
“…() suggest that a more precise distinction can be found when focusing on recent changes in anhedonia, which is more accurately captured by the Specific Loss of Interest and Pleasure Scale (SLIPS) and the Beck Depression Inventory's (BDI) anhedonia subscale (items 4, 12, and 21). Several of the studies indicating a positive relationship between anhedonia and STB used these measures (Gabbay et al., ; Loas, Lefebvre, Rotsaert, & Englert, ; Winer et al., ; Winer, Drapeau, Veilleux, & Nadorff, ; Yaseen et al., ; Zielinski et al., ), providing support for the hypothesis that increased risk of STB is associated with acute anhedonic state. However, these studies do not address the role of trait anhedonia.…”
Section: Introductionmentioning
confidence: 95%
“…Some studies found that State‐A (recent changes and acuity) was especially predictive of suicidal ideation independently of depressive symptoms (Ducasse et al, ; Hawes et al, ; Winer et al, ; Winer et al, ). Other studies found that State‐A mediated the positive association between depressive symptoms/perceived burdensomeness/thwarted belongingness and suicidality (Loas et al, ; Zielinski et al, ). In the current study, state anhedonia moderated the indirect association between stress and SI.…”
Section: Discussionmentioning
confidence: 95%
“…Anhedonia, defined as a lowered ability to experience pleasure, has been identified as a suicide risk factor (Loas, ). Recent works suggested taking into account the severity and the type of anhedonia when examining suicidal ideation (SI) (Ducasse et al, ; Loas et al, ). Anhedonia has been defined as both a state and a trait, dependent on whether it is thought of as an aspect of a depressive state or a personality trait (Loas & Pierson, ).…”
mentioning
confidence: 99%
“…As discussed, anhedonia has a relevant impact on patients’ quality of life. It worsens the rate of suicidal ideation in different samples and determines poor social functioning and higher and prolonged hospitalization …”
Section: Discussionmentioning
confidence: 99%